Genetic mapping of bovine T-cell receptor complex loci - Agaba, Morris; Kemp, Stephen J.; Barendse, W.; Teale, A.J. (Wiley, 1997)
Thymic-derived lymphocytes (T cells) recognize and respond to antigens through the mediation of the T-cell receptor complex. Here we report polymorphism at each of the five loci that encode the different components of the T-cell receptor complex in cattle. These genes were mapped on the bovine genome by genetic linkage analysis in the International Bovine Reference Panel (IBRP). These mapping data provide additional type I markers for linking the bovine genetic map with the human and mouse maps and also permit investigation of the effect of T-cell receptor polymorphism on immune responsiveness and disease susceptibility.